1995
DOI: 10.1073/pnas.92.26.12333
|View full text |Cite
|
Sign up to set email alerts
|

Temporally and spectrally resolved subpicosecond energy transfer within the peripheral antenna complex (LH2) and from LH2 to the core antenna complex in photosynthetic purple bacteria.

Abstract: We report studies ofenergy transfer from the 800-nm absorbing pigment (B800) to the 850-nm absorbing pigment (B850) of the LH2 peripheral antenna complex and from LH2 to the core antenna complex (LH1) in Rhodobacter (Rb.) sphaeroides. The B800 to B850 process was studied in membranes from a LH2-reaction center (no LH1) mutant of Rb. sphaeroides and the LH2 to LH1 transfer was studied in both the wild-type species and in LH2 mutants with blueshifted B850. The measurements were performed by using '100-fs pulses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
110
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 27 publications
17
110
1
Order By: Relevance
“…3B), we find that the population initially resides predominantly on B850, confirming our selective pumping condition. The spectral weight then shifts to B875, indicating forward B850 → B875 ET, within a few picoseconds, a timescale comparable to similar systems (24,25). However, even after 350 ps, a considerable amount of B850 population remains, indicating a backward B850 ← B875 ET, leading to a stationary B850∕B875 ratio after an equilibration dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B), we find that the population initially resides predominantly on B850, confirming our selective pumping condition. The spectral weight then shifts to B875, indicating forward B850 → B875 ET, within a few picoseconds, a timescale comparable to similar systems (24,25). However, even after 350 ps, a considerable amount of B850 population remains, indicating a backward B850 ← B875 ET, leading to a stationary B850∕B875 ratio after an equilibration dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…We use a specially designed femtosecond pumpprobe spectrometer, combining tunable narrowband pump with broadband white-light probe pulses, and introduce an analytical method based on derivative spectroscopy for disentangling the congested transient absorption spectra of LH1 and LH2 complexes. In previous femtosecond studies (24,25), the contributions of forward and backward ET to the observed LH2 ↔ LH1 equilibration dynamics could not be resolved, and therefore information on backward ET has only been obtained in an indirect and qualitative manner (20,26,27). With our approach, we are able to track the equilibration dynamics, determine both forward and backward ET rate constants, and quantify the final population equilibrium between B850 and B875 excitons (see Fig.…”
mentioning
confidence: 99%
“…For reviews see (van Grondelle and Novoderezhkin, 2006a;Sener et al, 2011;Strümpfer et al, 2012). Excitation transfer kinetics in the chromatophore was reported experimentally in (Woodbury and Parson, 1984;Visscher et al, 1989;Crielaard et al, 1994;Hess et al, 1994Hess et al, , 1995. Exciton migration across the network of light harvesting complexes in the chromatophore can be described by a rate matrix K which is constructed from inter-complex exciton transfer rates k IJ , the latter given by Equation (S6), as follows (Sener et al, 2010(Sener et al, , 2007 …”
Section: Stage I: Light Absorption Excitation Energy Transfer and Qmentioning
confidence: 99%
“…1). This assures efficient capture of light energy and rapid energy transfer from LH2 to LH1 and then to the reaction center (RC) (Hess et al 1995). Each light-harvesting complex is known to consist of oligomeric pairs of transmembrane proteins, termed α and β, to which BChls (a and b) and accessory Car pigments are noncovalently attached (Hawthornthwaite and Cogdell 1991).…”
Section: Introductionmentioning
confidence: 99%